2012
DOI: 10.7241/ourd.20124.78
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of Herpes zoster oticus in an immunocompetent patient

Abstract: IntroductionRamsay Hunt syndrome (RHS) is first described by James Ramsay Hunt in 1907 [1]. It is caused by the reactivation of latent varicella-zoster virus (VZV) that has remained dormant within sensory root ganglia (commonly the geniculate ganglion) of the sensory branch of the facial nerve. Involvement of sensory branch of the geniculate ganglion of facial nerve leads Herpes zoster (HZ) oticus which is also known as RHS. Individuals with decreased cell-mediated immunity resulting from carcinoma, radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Therefore, elderly patients should be recognized to prevent this virus risk and apt treatment must be initiated at the earliest. 14 Sebaceous cysts were observed only in 2 cases and were managed with complete excision.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, elderly patients should be recognized to prevent this virus risk and apt treatment must be initiated at the earliest. 14 Sebaceous cysts were observed only in 2 cases and were managed with complete excision.…”
Section: Discussionmentioning
confidence: 99%
“…[5,7] Persons with reduced cell-mediated immunity resulting from carcinoma, radiation therapy, chemotherapy, or human immunodeficiency virus (HIV) infection are particularly at risk. [8] However, it can also rarely be seen in immune-competent patients. [8] The thoracic segment is involved in the majority of herpes zoster cases.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…[8] However, it can also rarely be seen in immune-competent patients. [8] The thoracic segment is involved in the majority of herpes zoster cases. [2] It has been reported that the head and neck involvement of herpes zoster is 13-35%.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations